THE STUDING ANTIBACTERIAL AND IMMUNOPOTENTIAL ACTIVITY POLYPHENOL SUBSTAINTES OF EXTRAKTIS DUSCHEKIA VIRIDIS - Belyaebskya, S.Yu.; Kulagina, M.A.; Osolodchenko, T.P.; Radko, E.V.; Serbin, A.G.; Port, E.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Antibacterial and immunopotential activity of polyphenolic substaites from Duschekia viridis in museums's and clinical strains of microorganisms  was studies. Ethylacetac extractis of  ripe blossoms has antimicrobial activity to wide spectrum of microorganisms and in future can be used for introduction of new antibacterial and immunopotential drug.